Pentingnya Memahami Ma’na Dalam Berbahasa Arab (Jurnal Adabiya, 2020)
This study discusses the importance of understanding ma’na in Arabic, as well as trying to refute the accusation that Arabs are more concerned with the structure of the Language than they are from the Language. The method used in this study is descriptive analysis by citing relevant language leaders’ thoughts. Further proof of the case is in accordance with Arabic grammar and other proofs are also carried out in “un- derstanding Ma’na is very important in language” is also evidenced in the verses of the Arabic poetry. The results of this study prove that grammar appears to maintain the integrity of language, but grammar cannot prevent the occurrence of a speech that is sometimes different from the rules that have been compiled. Ma’na, which is contained in Arabic sentences, is very diverse, so this grammar of various Arabic languages results in accusations that Arabs are more concerned with grammar.